Problematika Transformasi Sertipikasi Tanah Digital - Huda, Nurul; Wandebori, Harimukti (Sekolah Tinggi Pertanahan Nasional, 2021)
In an effort to realize good and equitable services to all communities, the Ministry of ATR/BPN seeks to become a transparent and accountable institution or known as Good Governance. As an effort to realize this, digital land certification services are one of the steps towards good governance. This study aims to find out the problems faced in realizing digital certificates. The research method was carried out qualitatively, data was presented descriptively, while data collection was carried out through interviews with several respondents, namely the community and employees in the Kerawang Regency Land Office. The results of the study show that several obstacles in digital certificates are caused by internal factors including those related to human resources who are not entirely able to use technology/information, limited office infrastructure, data that has not been integrated and the need for definite checks related to documents in land certificates. While some external factors are related to the community and other agencies, namely not all people have the ability to use information technology, not all people have digital equipment, besides the problem with other agencies, namely the unavailability or integration of data in one system. Some of these problems have caused the digital land certification process to take a long time and do not meet the expected standards.